JANGKUNGAN PERSPEKTIF HUKUM WARIS ISLAM - Ulinnuha; Fetri Fatorina (Faculty of Social, Economics and Humanities, 2023)
This research aims to understand the view of Islamic inheritance law on the use of the anchor system in the division of inheritance which is still applied in the community today. The research method used is field research with a focus on the process of distributing inheritance. The approach applied is a normative approach. Data was collected through observation, interview, and documentation techniques. The results showed that from the perspective of Islamic inheritance law, the use of the stilt system is legally valid. This is due to the interpretation of jangkungan in the context of Islamic inheritance law, where both the wife and husband have the rights stipulated in both fiqh and law to get a share of the inheritance. Although the division may not fully comply with the provisions in fiqh and Islamic inheritance law, this does not affect the legal validity of jangkungan in the inheritance division system. The reason is that the system of inheritance distribution applied in the community is the result of a combination of the provisions in Islamic inheritance law with the Western system of inheritance law.